Guidance in the diversity: a glance from Latin America - González Bello, Julio R. (2007)
Guidance and Diversity, for the majority of the European countries and North America , are related to the attention to children and young people with special necessities, that are attend in an educative institution and for those who are elaborated educative programs directed to obtain one better adaptation to the prevailing social system. In most of the cases is considered that the problematic of the special necessities is imputable to genetic or personal factors that only respond to internal factors to the individuals that display them avoiding the external factors that in some cases can be more decisive determinants at the time of the conductual manifestation. In this work is pleaded because the professionals of the Guidance, as much private or public scenes of the European countries, make more specific considerations at the time of taking care of children, young people and adults, as immigrants, coming of Latin America . In an ample sense one sets out to make Guidance in the Diversity more than Guidance for the Diversity under the conception of a Guidance for All which implies the elimination of the expression "special necessities", whose connotation in our countries is not most appropriate, and than it includes the idea of an Ethnic Guidance. Perhaps the best way of boarding of these conceptions is promoting a process of Guidance from the School and not only in the School.